The role of follicular T helper cells in patients with malignant lymphoid disease. Issue 7 (9th August 2017) - Zhou, Dong-Ming; Xu, Yan-Xia; Zhang, Li-Ying; Sun, Yu; Wang, Zi-Yan; Yuan, Yu-Qing; Fu, Jin-Xiang
ABSTRACT: Objectives: To investigate the dynamic change of follicular T helper cells (TFH ) in patients with malignant lymphoid disease (MLD) and to explore its clinical significance. Methods: The dynamic change of TFH cells, ICOS + - and PD-1 + TFH cells at pretreatment and different treatment periods was determined by flow cytometry in 85 MLD patients. Concentration of interleukin 21 (IL-21) was evaluated by ELISA, and the correlation between clinical prognosis and the ratio of TFH cells was analyzed. Results: Significantly increased ICOS + - and PD-1 + TFH cells were found in MLD patients at pretreatment compared to healthy controls. Decreased or even close to normal levels of ICOS + - and PD-1 + TFH cells were found at the end of treatment. However, in the patients with progressive disease, high levels of ICOS + - and PD-1 + TFH cells were found. Moreover, a significantly increased plasma IL-21 level was found in MLD patients. Negative correlation was found between the level of ICOS + -, PD-1 + TFH cells, as well as IL-21 and the prognosis of MLD. Conclusions: Significantly increased TFH cell ratios were found in patients with MLD, and decreased TFH cells ratios could be expected in those treatment-effective patients, which could be used as the therapeutic efficacy index.